Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (Sexual cultures, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

Miroir bisexuel: une socio-anthropologie de l'invisible - Deschamps, Catherine (Modernes, 2002)
Les bisexuels, ça n'existe pas ! ". A-t-on déjà entendu proférer de tels propos sur les noirs, les blancs, les juifs, les femmes ou les gays ? Étrange démarche que de produire du sens au sujet d'une population dont la présence même est mise en doute. Mais la demande de preuve adressée aux femmes et aux hommes bisexuels a pour leurs émetteurs une fonction : les protéger des doutes identitaires qu'ils suscitent. Fondé sur l'observation de la seule association bisexuelle française ayant pignon sur rue, le présent ouvrage met l'accent en priorité sur les caractéristiques identitaires, politiques et culturelles. La bisexualité apparaît alors comme le terrain d'observation privilégié de l'ensemble des orientations sexuelles. Elle permet de la sorte une déconstruction des normes les plus insidieuses, communes à toutes et à tous. Car la bisexualité, plus une identité pertinente en elle-même, est une délatrice de l'invisible, qui ouvre, non plus à une approche diffractée de la différence, mais à une compréhension holistique du phénomène des sexualités.
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

From Social Construction to Social Justice: Transforming How We Teach about Intersexuality - Koyama, Emi; Weasel, Lisa (Women's Studies Quarterly, 2002)
Keywords: LGBTQIA2+; approches et analyses; capacitisme; corps; cours; discipline; intersexuation; justice sociale; premier cycle; pédagogie; santé; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Re-orienting desire: The gay international and the arab world - Massad, Joseph (Public Culture, 2002)
Keywords: approches et analyses; cours; discours dominant; fem3400; identités LGBTQIA2+; islam; premier cycle; racisme; ressource en ligne; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Genre et technosciences : les rôles féminins dans l'univers de quatre jeux vidéo - Trudeau, Judith (Université du Québec à Montréal, 2002)
Keywords: IREF; approches et analyses; discipline; genre; identités LGBTQIA2+; inégalités; jeux vidéos; mémoires/thèses; rapports sociaux de sexe; science politique; science politique et droit; stéréotypes de genre; systèmes d'oppressions; thématiques